A systemic functional analysis of conjunction in "Au Revoir les Enfants" - Mubenga, Kajingulu Somwe (Stellenbosch Papers in Linguistics Plus, 2014)
This paper involves an analysis of conjunctive cohesive markers in the subtitled version of the film Au Revoir les Enfants (Malle 1989) from a systemic functional perspective. The underlying hypothesis is that in the translation of this film from French into English some conjunctive cohesive markers are omitted because of time and space constraints (Gottlieb 1992) as well as the principle of relevance (Bogucki 2004) imposed on the subtitles. Thus, four types of coordinators (i.e. et, mais, car and donc) and five types of subordinators (i.e. que, si, quand, comme and parce que/ puisque) are analysed at the clause and clause-complex level, respectively. The omission of these conjunctions is accompanied by shifts and transformations at the lexical, phonological and syntactic levels. On the basis of these shifts and transformations, twelve strategies are developed to serve as models or teaching mechanisms in subtitler training.